2021
DOI: 10.1140/epjp/s13360-021-01336-9
|View full text |Cite
|
Sign up to set email alerts
|

RDX remote Raman detection on NATO SET-237 samples

Abstract: Ultraviolet Raman spectroscopy measurements have been taken at DLR in Lampoldshausen to detect NATO SET-237 standard samples of RDX. The main goal was to quantify the minimum requirements for an unambiguous identification in remote detection (60 cm distance) with a commercial Czerny–Turner spectrometer coupled with a CCD camera. Well-defined distribution of explosives on surfaces was tested as standardized samples. Therefore, Raman spectra of RDX have been acquired for different sample concentrations (50, 250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A detailed description of this methodology is provided by Schnürer et al [14]. The new set of samples requested was in smaller concentration comparing the previous one prepared on 2019 [7]. Smaller concentrations (50, 30, 20, 10, 5 and 1 µg/cm 2 , respectively) were required to further test the sensitivity limits.…”
Section: Explosive Nato-set-237 Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed description of this methodology is provided by Schnürer et al [14]. The new set of samples requested was in smaller concentration comparing the previous one prepared on 2019 [7]. Smaller concentrations (50, 30, 20, 10, 5 and 1 µg/cm 2 , respectively) were required to further test the sensitivity limits.…”
Section: Explosive Nato-set-237 Samplesmentioning
confidence: 99%
“…Native fluorescence was summing up to the room light adding extra disturbances. Native fluorescence can come from the measured compounds (in this case only from the warfare agents' simulants, since it was demonstrated that none of the tested explosives offered detectable fluorescence signal [7]) and from the substrates simultaneously. The fluorescence interference can play a very significant role since the lased-induced fluorescence (LIF) signal is much stronger than the Raman [1].…”
Section: Background Subtractionmentioning
confidence: 99%
See 2 more Smart Citations
“…High-power single-frequency laser systems have become increasingly attractive thanks to their high spatial and temporal coherence, which has enabled technological advances in many applications such as high-resolution spectroscopy, remote sensing, non-linear frequency conversion, and holography. In particular, remote Raman spectroscopy [1,2] is witnessing increasing use, especially in military and defense applications, to detect and identify chemical, biological, radiological, nuclear, or explosive materials [3]. The Raman signal strength (intensity) is directly proportional to the power of the laser used to excite the sample, and inversely proportional to the laser wavelength [4].…”
Section: Introductionmentioning
confidence: 99%